1992
DOI: 10.1089/thy.1992.2.247
|View full text |Cite
|
Sign up to set email alerts
|

T Cells and Human Autoimmune Thyroid Disease: Emerging Data Show Lack of Need to Invoke Suppressor T Cell Problems

Abstract: Human T cells recognize self and foreign antigens when such antigens are processed into small peptides and bound to molecules coded for by genes of the HLA region on chromosome 6. The part of the T-cell surface which is responsible for such recognition is a set of molecules coded for by a variety of genes and known as the T-cell-receptor complex. In animal models, T cells are able to transfer autoimmune thyroiditis and T cells have, therefore, long been implicated in the etiology of human autoimmune thyroid di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 150 publications
(153 reference statements)
0
23
0
Order By: Relevance
“…This suggests that the 53 codon 72 Arg/Pro polymorphism could represent a viable candidate genetic marker for the purpose of predicting the increased susceptibility to the development of HT. HT and GD are both AITD, and undoubtedly, humoral as well as cell-mediated immunity play an important role in the development of both disorders (7,8). It should be recognized, however, that apoptosis also contributes to an individual's susceptibility to AITD, at least partially by way of regulating the maturation and control of the immune response mediated by both T and B lymphocytes (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the 53 codon 72 Arg/Pro polymorphism could represent a viable candidate genetic marker for the purpose of predicting the increased susceptibility to the development of HT. HT and GD are both AITD, and undoubtedly, humoral as well as cell-mediated immunity play an important role in the development of both disorders (7,8). It should be recognized, however, that apoptosis also contributes to an individual's susceptibility to AITD, at least partially by way of regulating the maturation and control of the immune response mediated by both T and B lymphocytes (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Intrathyroidal lymphocyte infiltration, the pathognomonic feature of AITD, is typically composed of T cells and B cells, implying a contribution to the pathogenesis of both disorders from cell-mediated as well as humoral immunity (7). Typically such B cells are able to produce Abs, such as AMA and antithyroglobulin Ab (ATA), and TRAb (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…Other workers (48) make convincing arguments against the former suppressor cell defect theory, suggesting that in the absence of definitive prospective studies with functional assessments, the observed cell changes reflect only a nonthyroidal nonspecific immune response. They further emphasize the role of cytokines derived from cells as modify¬ ing the immune response, through effects on either or cells or thyrocytes (48,49). Most investigators do agree that cells play a primary role in the autoimmune process leading to thyroid disease, with cell-mediated cytotoxic thyrocyte destruction in Hashimoto's disease and a more complex series of events appearing in Graves' disease.…”
Section: In Vitro Immunosuppressive Actions Of Antithyroid Drugsmentioning
confidence: 99%
“…Clinically, active GD patients virtually always appear hyperthyroid, whereas HT patients may be euthyroid, hypothyroid, or occasionally, hyperthyroid. Although the histopathological appearance of both disorders are different in some ways, the thyroid glands of patients suffering from each disorder all present with a rather diffuse cellular infiltration, which is composed of T-and B-cells and other inflammatory cells (especially macrophages), this suggesting the contribution of cell-mediated immunity, as well as humoral immunity, to the pathogenesis of these two diseases [1][2][3]. In practice, an abundance of antibodies (Abs) against certain thyroid-specific components, such as thyrotropin receptor, microsome/thyroid peroxidase and thyroglobulin, can be measured from the sera of the majority of individuals afflicted with either GD or HT [4,5].…”
Section: Introductionmentioning
confidence: 99%